RNA-Seq Analysis of Diverse Rice Genotypes to Identify the Genes Controlling Coleoptile Growth during Submerged Germination - Hsu, Sheng-Kai; Tung, Chih-Wei (Frontiers in Plant Science, 2017)
The rate of coleoptile elongation varies between different rice varieties that are grown under water during the germination stage. Compared to sensitive varieties, submergence-tolerant rice exhibits substantial coleoptile elongation in order to uptake oxygen (O2) from the surface and thus have a better chance to survive water stress. We conducted RNA-seq analysis in order to investigate seven-day-old shoot transcriptome dynamics in six rice genotypes that exhibit different coleoptile elongation rates under water. This enabled us to identify the genes involved in photosynthesis, lipid metabolism, glycolysis, anaerobic fermentation, hormone synthesis, cell wall growth, and expression profiling, and to demonstrate that these genes are differentially regulated within, and between, genotypes. Further, in addition to determining how allelic variation affects anaerobic germination, we compared the expression patterns and genomic sequences of six genotypes; this enabled us to discover that some genes carry small-to-large deletions in the coding region of sensitive varieties. These structural variations may explain the absence of transcripts in the dataset, as well as the failure of sensitive variety to respond to submergence. On the basis of these results, we hypothesize that transcriptional regulation enhances coleoptile elongation. Although this is an area for future research, the outcome of this study is expected to facilitate rice breeding for direct-seeding.